Adult congenital heart disease: frequency, risk factors and outcomes of acute kidney injury in postoperative period - Memon, Muhammad Kamran Younis (Indian J Thorac Cardiovasc Surg, 2020)
BACKGROUND: Acute kidney injury (AKI) after surgery for congenital heart disease (CHD) in adults is poorly studied despite being well-recognized as a postoperative complication after cardiac surgery in adults. The primary aim of our study was to determine the frequency of AKI in adults undergoing surgery for CHD. We also aimed to determine risk factors and predictors of AKI in this patient population, and to explore outcomes in terms of duration of mechanical ventilation, intensive care unit (ICU) stay, and hospital stay. METHODS: This retrospective cross-sectional study included all adult patients (18 years) who underwent cardiac surgery with cardiopulmonary bypass for their congenital heart problems from January 2011 to December 2016 in a tertiary-care private hospital. RESULTS: A total of 166 patients with a mean age of 32.05 ± 12.11 years were included in this study. The postoperative course was complicated by AKI in 29.5% of patients. Thirty-two percent of these patients had moderate-to-severe kidney disease. Two patients (4%) developing AKI required renal replacement therapy in the form of transient hemodialysis. All patients in our study showed complete resolution of AKI, with no mortalities in the postoperative period. On univariable analysis, (Risk adjusted classification for congenital heart surgery-1) RACHS-1 category 2 and 3, aortic valve replacement, preoperative creatinine clearance, ventricular septal defect closure, cardiopulmonary bypass time, aortic cross-clamp time, intra-operative excessive blood loss, intra-operative ionotropic score, and postoperative hypotension were found to be significant predictors for the development of AKI. On age-adjusted multivariable analysis, RACHS-1 category 2 (OR = 3.49; CI = 1.22–9.95) and category 3 (OR = 3.28 = 1.15–9.36), and intra-operative excessive blood loss (OR = 2.9; CI = 1.07–7.85) were significant predictors of AKI development in the postoperative period. Moreover, development of AKI postoperatively was a predictor of a significantly longer cardiac intensive care unit (CICU) stay (OR = 1.21; CI = 1.08–1.37). CONCLUSION: We found that preoperative creatinine clearance, ACC time, intraoperative excessive blood loss, and RACHS-1Category 2 and 3 are potential risk factors for postoperative AKI development. Moreover, patients who develop AKI are likely to have a significantly longer CICU stay. Our study has tried to fill the lacunae with regard to AKI in adults undergoing surgery for CHD. However, there is a need for more studies with larger cohorts involving more complex surgeries to truly estimate the incidence and potential risk factors for AKI in this group of patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12055-020-00926-z) contains supplementary material, which is available to authorized users.